Effective selection of countries in sub-Saharan Africa for independent wind power producers using a multiple criteria decision analysis - Gildenhuys, Enelge (Department of Construction Economics and Management, 2018)
Subjective decision making can lead to results that are difficult to justify in cases where the outcome is unfavourable. This is the case in the wind energy industry where wind independent power producers (IPPs) assess new market entry opportunities. Decision analyses methods can assist decision makers when faced with difficult choices such as which market to enter. Multi Criteria Decision Analyses or MCDA is one of the most preferred of many different decision analyses methods. MCDA ranks a set of criteria in order of importance and then, based on the results, ranks alternatives. There are many MCDA methods available and the most often used include the analytical hierarchy process (AHP), multi-attribute utility theory (MAUT), preference ranking organization method for enrichment evaluation (PROMETHEE), elimination and choice translating reality (ELECTRE) and technique for order preference by similarity to ideal solution (TOPSIS). In this study a combination of MCDA methods are used to rank Sub-Saharan African countries based on preference for new market entry for wind IPPs. Nineteen different criteria were identified through a thorough literature review that were included in the analyses. The nineteen criteria were categorised into economic, technical, political and social criteria. The study was divided into two phases. In the first phase an industry expert survey was concluded and resulting from this survey the AHP was used to rank the criteria in order of importance. In the second phase PROMETHEE was used to rank seven Sub-Saharan African countries from most to least favourable for IPP market entry. The expert survey and AHP showed that political and economic criteria are considerably more important than technical and social criteria. Governments have the ability to change both the economic and political landscape and should do so if they want to attract wind IPPs. On the other hand, technical and social criteria are more difficult for governments to change but these do not have as significant impact on market attractiveness. The PROMETHEE model ranked South Africa as the most favourable market for wind IPPs to enter followed by Ethiopia, Namibia, Kenya, Mozambique, Nigeria and lastly Zambia. The top two countries both have very strong natural wind resources and South Africa is the only country with incentives specifically and exclusively for on grid renewable energy. The least favourable two countries, namely Nigeria and Zambia, have almost no wind resource and a weak economic environment. Future research can use MCDA methods, such as AHP and PROMETHEE, to assist in the evaluation of different market entry opportunities. These methods can also be adapted to investigate opportunities at country level i.e. analyse and compare different states/provinces with each other.